FEATURE EXTRACTION FROM FUSION OF IRIS AND PALMPRINT BIOMETRIC IMAGES FOR RECOGNITION - Pranjali G. Adey; Dr. D. V. Jadhao (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper presents fusion of two biometric traits, i.e., iris and palmprint, at feature level fusion that combines the information from iris and palmprint biometric which can achieve better performance, which may not be possible using a single biometric technology.The features are extracted from the pre-processed images of iris and palmprint. This system extracts Gabor texture from the pre-processed iris and palmprint images. The feature vectors attained from different methods are in different sizes and the features from equivalent image may be correlated, hence wavelet-based fusion technique is used to fuse both images. Finally the feature vector is matched with database template using Euclidean distance formula.The system is authenticated for their accuracy on PolyU palm printdatabase fused with IITK iris database of 125 users. The experimental results demonstrated that the proposed multimodal biometric system achieves recognition accuracy of 99.2% and with false rejection rate (FRR) of 1.6% and false acceptance rate (FAR) of 6.3%.